Immunological and Genetic Markers of Rheumatoid Arthritis Among Women in North India: A Case-Control Study - J. Samuel Kamanda; Atul Khajuria; Eric Kwasi Elliason; Stephen Monday (International Journal of Genetic Modifications and Recombinations, 2025)
Background: Rheumatoid arthritis (RA) is an autoimmune disease systemically afflicting women marked by chronic inflammation around the involved joints leading to joints destruction. It has both endocrinological and immunological associations as well as genetic associations but data pertaining to women of North India is scanty. Objective: This case-control study was done to evaluate the presence and significance of major immunological and genetic markers of RA in North Indian women with the disease and comparing them with healthy controls to establish potential links of immunological markers and genetic markers with disease susceptibility. Methods: A total of 790 participants were enrolled (570 RA cases, 220 controls). Immunological markers RF, ACPA, ESR and CRP were quantified. Genetic polymorphisms of HLA-DRB1, PTPN22, STAT4, TRAF1/C5 and IL23R were analyzed using PCR based methods. Significant differences were calculated using logistic regression and chi-square tests. Results: The prevalence of RF was 73.7%, ACPAs were 66.7%, ESR elevation was 59.6% and CRP was 54.4% compared to controls indicating significant differences. Moreover, cases were also noted to harbor risk alleles of HLA-DRB1 (56.1), PTPN22 (36.8), STAT4 (31.6), TRAF1/C5 (26.3) and IL23R (15.8) confirming their association with RA at significantly higher odds of 1.9 to 5.1. Of the antibodies studied, greatest association was noted with ACPAs (OR=5.1, p<0.001) followed by RF then HLA-DRB1. Conclusion: The results of the study suggest that the clinical and genetic markers of immunity are strongly related to the susceptibility of rheumatoid arthritis in women living in the northern part of India. Implementation of serological testing along with genetic profiling could improve the management of RA in this population through early diagnosis and tailored treatment plans.
Keywords: ACPAs; Autoimmune disease; Genetic polymorphism; HLA-DRB1; Immunological markers; North Indian women; inflammation; rheumatoid arthritis